Social-ecological inventory in a postdisaster context: the 2016 Kaikōura earthquake, Aotearoa-New Zealand - Nicholas A. Cradock-Henry; Franca Buelow; Joanna Fountain (Ecology and Society, 2019)
Natural hazards continue to have adverse effects on communities and households worldwide, accelerating research on proactively identifying and enhancing characteristics associated with resilience. Although resilience is often characterized as a return to normal, recent studies of postdisaster recovery have highlighted the ways in which new opportunities can emerge following disruption, challenging the status quo. Conversely, recovery and reconstruction may serve to reinforce preexisting social, institutional, and development pathways. Our understanding of these dynamics is limited however by the small number of practice examples, particularly for rural communities in developed nations. This study uses a social-ecological inventory to document the drivers, pathways, and mechanisms of resilience following a large-magnitude earthquake in Kaikōura, a coastal community in Aotearoa New Zealand. As part of the planning and implementation phase of a multiyear project, we used the tool as the basis for indepth and contextually sensitive analysis of rural resilience. Moreover, the deliberate application of social-ecological inventory was the first step in the research team reengaging with the community following the event. The inventory process provided an opportunity for research partners to share their stories and experiences and develop a shared understanding of changes that had taken place in the community. Results provide empirical insight into reactions to disruptive change associated with disasters. The inventory also informed the design of targeted research collaborations, established a platform for longer-term community engagement, and provides a baseline for assessing longitudinal changes in key resilience-related characteristics and community capacities. Findings suggest the utility of social-ecological inventory goes beyond natural resource management, and that it may be appropriate in a range of contexts where institutional, social, and economic restructuring have developed out of necessity in response to felt or anticipated external stressors.